Rethinking Japanese Feminisms - Bullock, Julia C.; Kano, Ayako; Welker, James (University of Hawaii Press, 2018)
Rethinking Japanese Feminisms offers a broad overview of the great diversity of feminist thought and practice in Japan from the early twentieth century to the present. Drawing on methodologies and approaches from anthropology, cultural studies, gender and sexuality studies, history, literature, media studies, and sociology, each chapter presents the results of research based on some combination of original archival research, careful textual analysis, ethnographic interviews, and participant observation.The volume is organized into sections focused on activism and activists, employment and education, literature and the arts, and boundary crossing. Some chapters shed light on ideas and practices that resonate with feminist thought but find expression through the work of writers, artists, activists, and laborers who have not typically been considered feminist; others revisit specific moments in the history of Japanese feminisms in order to complicate or challenge the dominant scholarly and popular understandings of specific activists, practices, and beliefs. The chapters are contextualized by an introduction that offers historical background on feminisms in Japan, and a forward-looking conclusion that considers what it means to rethink Japanese feminism at this historical juncture.Building on more than four decades of scholarship on feminisms in Japanese and English, as well as decades more on women’s history, Rethinking Japanese Feminisms offers a diverse and multivocal approach to scholarship on Japanese feminisms unmatched by existing publications. Written in language accessible to students and non-experts, it will be at home in the hands of students and scholars, as well as activists and others interested in gender, sexuality, and feminist theory and activism in Japan and in Asia more broadly